Technology education in elementary school using the example of 'learning robots' – development and evaluation of an in-service teacher training concept - Janicki, Nicole; Tenberge, Claudia (Australasian Journal of Technology Education)
The context of the study is the increasing digitalisation of the living environment of primary school students, which is to be introduced into primary schools according to theoretical and educational policy guidelines. In this regard, further teacher training on digital media in classrooms are particularly relevant, on the one hand to promote teachers’ digital-related pedagogical knowledge and content knowledge (DPaCK). On the other hand, studies also reveal positive correlations among teacher training, teaching activities, and students’ learning outcomes. In-service teacher training courses with adaptive support by a trainer in particular have proven to be effective. Against the background of various research studies on professional development of teachers, a corresponding model of tripartite learning outcomes has been established and serves as a broad theoretical framework. However, the specific relationship between in-service teacher training with adaptive support, DPaCK, and computational thinking of primary school students in the context of the German primary school subject Sachunterricht has not been sufficiently studied. Therefore, the following research questions can be derived: (1) To what extent does training with adaptive support on the topic of learning robots contribute to the development of teachers’ DPaCK? (2) Which effects can be ascertained on the students’ computational thinking in technology-related Sachunterricht? To investigate this relationship, an intervention study in a pre-post design with an experimental group, a control group, and a baseline is appropriate. As results are not yet available at this point, the present paper focuses on the presentation of the theoretical background and empirical approaches.
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der 31. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe vom 27. bis 29.09.2023 an der Universität Siegen - Janicki, Nicole

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der gemeinsamen Jahrestagung der DGTB und GATWU vom 21. bis 22.09.2023 an der Universität Potsdam - Janicki, Nicole

Technology Education in Elementary School Using the Example of 'Learning Robots' – Development and Evaluation of an In-Service Teacher Training Concept. - Janicki, Nicole; Tenberge, Claudia

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der 31. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) vom 09. bis 12.03.2022 in Köln - Janicki, Nicole

Entwicklung und Evaluation eines Fortbildungskonzepts im Kontext der technischen Bildung an Grundschulen am Beispiel von Lernrobotern - Janicki, Nicole (Technik: Verstehen wir, was wir nutzen!? - Tagungsband zur 23. Jahrestagung der Deutschen Gesellschaft für Technische Bildung in Mannheim vom 24.-25. September 2021.)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots